Sosialisasi Pembuatan Eco-Paving Block Berbasis Serbuk Cangkang Telur sebagai Material Konstruksi Ramah Lingkungan - Y. Sulistiyohadi; Era Agita Kabdiyono; Jalaludin Jalaludin; Achmad Sarwiji; Sigit Ary Cahyon; Tegar Rafii Fadh Lullah (Asosiasi Dosen Muda Indonesia, 2026)
Eggshell waste is an organic waste commonly generated from households, school canteens, restaurants, and food industries, yet its utilization remains limited. Eggshells contain calcium carbonate (CaCO₃), which has the potential to be used as a partial cement substitute in environmentally friendly construction materials. This community service activity aims to improve the knowledge and skills of students at SMK Negeri 4 Kota Tangerang in utilizing eggshell waste as a mixture material for eco-concrete or eco-paving block production. The implementation method used a participatory approach, including preliminary observation, socialization of green technology concepts, training in processing eggshells into powder, product-making demonstrations, hands-on practice, discussion, documentation, and activity evaluation. The activity data were analyzed descriptively and qualitatively based on observation results, participant responses, documentation, and evaluation of participants’ understanding. The results show that participants gained knowledge about green technology, organic waste management, eggshell processing stages, and the potential of eggshell powder as an alternative material for non-structural construction products. This activity contributes to increasing environmental awareness and strengthening students’ practical skills in processing waste into value-added materials. The originality of this activity lies in the integration of environmental education, appropriate technology, and practice-based learning in introducing eggshell powder-based eco-paving block innovation within vocational education.